More than memory impairment in voltage‐gated potassium channel complex encephalopathy. (1st July 2014) - Bettcher, B. M.; Gelfand, J. M.; Irani, S. R.; Neuhaus, J.; Forner, S.; Hess, C. P.; Geschwind, M. D.
<x xml:space="preserve">Abstract</x> Background and purpose Autoimmune encephalopathies (AEs) are a heterogeneous group of neurological disorders that affect cognition. Although memory difficulties are commonly endorsed, few reports of AEs inclusively assess all cognitive domains in detail. Our aim was to perform an unbiased cognitive evaluation of AE patients with voltage‐gated potassium channel complex antibodies (VGKCC‐Abs) in order to delineate cognitive strengths and weaknesses. Methods Serial VGKCC‐Ab AE subjects (n = 12) were assessed with a comprehensive evaluation of memory, executive functions, visuospatial skills and language. Clinical magnetic resonance imaging (MRI) (n = 10/12) was evaluated. Five subjects had serial cognitive testing available, permitting descriptive analysis of change. Results Subjects demonstrated mild to moderate impairment in memory (mean Z = −1.9) and executive functions (mean Z = −1.5), with variable impairments in language and sparing of visuospatial skills. MRI findings showed T2 hyperintensities in medial temporal lobe (10/10) and basal ganglia (2/10). Serial cognitive examination revealed heterogeneity in cognitive function; whereas most patients improved in one or more domains, residual impairments were observed in some patients. Conclusions This study augments previous neuropsychological analyses in VGKCC‐Ab AE by identifying not only memory and executive function deficits but also language impairments, with preservation of visuospatial functioning. The study further highlights the importance of domain‐specific testing to parse out the complex cognitive phenotypes of VGKCC‐Ab AE.